Pemanfaatan Batu Sungai Apanang Kecamatan Marioriwawo Kabupaten Soppeng Sebagai Agregat Pada Campuran AC-BC - Randi Frimus Madallo; Robert Mangontan; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Road construction generally uses materials that come from nature and until now almost all road infrastructure works have brought in materials from other places. This study was intended to test the characteristics of the AC-BC mixture using the Apanang River aggregate based on laboratory testing. The test method used is the conventional marshall test which is used to obtain the KAO value, after that, the test object is made for the KAO to obtain the Marshall Residual Stability. The test results show that the aggregate characteristics of the Apanang River, Soppeng Regency, meet the Bina Marga Specifications standard as an ingredient for the AC-BC mixture. In accordance with the results of the conventional Marshall test, the values ​​of VIM, VMA, stability, flow and VFB meet the General Specifications of Highways in 2018. And from the results of the Marshall Immersion test, a value of 92.59% is obtained with an asphalt content of 6.00% and has met the General Specifications. Highways in 2018.